Proceedings of the12th International Working Conference on Stored Product Protection (IWCSPP) (2018)
The severity of postharvest losses varies considerably depending on storage method and prevalence of storage insect pests known to bore into storage bags. Polypropylene (PP) bags used by smallholder farmers in Nigeria do not provide effective protection for stored produce due to insect boring activities. Deltamethrin incorporated polypropylene, ZeroFly® (ZF) and ZeroFly® Hermetic Storage Bags are technologies with potential to improve protection of stored food commodities against insect attack. Therefore, a 12-month study was conducted in Ibadan, Nigeria to determine the suitability and potential of combined postharvest bag technologies involving ZeroFly® (hermetic and non-hermetic) bags for smallholder farmers when exposed to Sitophilus zeamais and Prostephanus truncatus infestation pressure. Cleaned but un-fumigated 50-kg lots of maize were used to fill bags in each of the following 8 treatments — PP and ZF bags alone, diatomaceous earth-treated maize in PP and ZF bags, single and double hermetic liners in ZF bags, single hermetic liner in PP bags and lastly PICS bags. Results obtained over a 12-month period showed infestation by S. zeamais, Tribolium castaneum, Cryptolestes ferrugineus and Liposcelis spp and abundance of insect increased with storage period in PP and ZF bags without liner. The percentages of insect damaged kernels by number (IDK) were higher in PP and ZF bags without liner and were 5.4 and 16.9%, respectively; in ZeroFly bags with hermetic liners, these values were ~ 0.5%. The PP and ZF bags without liner also had higher weight loss values of 1.4 and 6.7%, respectively compared with ZeroFly bags with hermetic liners and PICS bags which had a relatively lower weight loss of <0.2%. These results indicate that the ZeroFly Hermetic bag mitigates insect infestations, thereby offering a suitable alternative towards achieving significant reduction in postharvest losses during storage.